2010
DOI: 10.4049/jimmunol.0903437
|View full text |Cite
|
Sign up to set email alerts
|

High-Affinity B Cell Receptor Ligation by Cognate Antigen Induces Cytokine-Independent Isotype Switching

Abstract: The selection of an appropriate Ig isotype is critical for an effective immune response against pathogens. Isotype regulation is sensitive to external signals, particularly cytokines secreted by Th cells. For example, IL-4 induces isotype switching to IgG1 via a STAT6-dependent signaling pathway. In this study, we show that BCR ligation also induces IgG1 switching in mouse B cells. The extent of switch induction by Ag is affinity-dependent, and high-affinity Ag binding leads to IgG1 switching levels comparable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…By contrast, the non-canonical NF-κB pathway in these B cells was normal and would have mediated – perhaps in a compensatory manner – germline Iγ1-Sγ1-Cγ1 transcription. Consistent with this notion, this transcription process is critically regulated by the κB sites in the Iγ1 promoter and the 3′ locus control region (71, 72), and can be induced by BCR crosslinking (13, 73). The normal non-canonical NF-κB pathway would also support homeostasis of Igh +/ C γ 1-cre Rab7 fl/fl B cells.…”
Section: Discussionmentioning
confidence: 64%
“…By contrast, the non-canonical NF-κB pathway in these B cells was normal and would have mediated – perhaps in a compensatory manner – germline Iγ1-Sγ1-Cγ1 transcription. Consistent with this notion, this transcription process is critically regulated by the κB sites in the Iγ1 promoter and the 3′ locus control region (71, 72), and can be induced by BCR crosslinking (13, 73). The normal non-canonical NF-κB pathway would also support homeostasis of Igh +/ C γ 1-cre Rab7 fl/fl B cells.…”
Section: Discussionmentioning
confidence: 64%
“…The cytokine profile of WAS patients shows an impairment in the production of Th1 cytokines [7] that could explain their reduced switching to IgG2 subclass. Moreover, the isotype-switching outcome is also influenced by two additional factors: cell division [55] and antibody affinity to antigens [56]. The defective proliferation of memory and natural effector B cells and the reduced affinity maturation found in WAS might contribute to these alterations in class switching.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a report has shown that one species CpG-ODN can directly stimulate mice B cells to switch isotype independence on Th1 or Th2 cytokines, 38 moreover, BCR ligation represents a novel pathway for Ag-induced IgG switch, that does not require additional cytokine signals. 39 It would be a hypothesis to explain why Th1 cytokines do not influence IgG antibody switching.…”
Section: Discussionmentioning
confidence: 99%